The Influence of Brand Experience, Brand Trust, Brand Satisfaction, and Complaint Handling on Brand Loyalty for MS Glow Skincare products - Zakiyah, Hanifa Shafa; Rahayu, Tri Septin Muji; Handayani, Erna; Zamakhsyari, Luthfi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of brand experience, brand trust, brand satisfaction, and complaint handling on MS Glow Skincare brand loyalty. This type of research is quantitative, using a purposive sampling technique, by collecting data through an online questionnaire distributed via goggle form to MS Glow Skincare consumers. Descriptive verification analysis uses multiple linear regression analysis, with a sample size of 150 respondents for this research. The method used is SPSS version 26. The results of the research are (X1) Brand experience has a positive and significant influence on brand loyalty, (X2) Brand trust has a negative and no significant influence on brand loyalty, (X3) Brand satisfaction has a positive and significant influence on loyalty brand, (X4) Complaint handling has also been proven to have a positive and significant effect on brand loyalty